Evaluating potential biomarkers of cachexia and survival in skeletal muscle of upper gastrointestinal cancer patients. Issue 1 (31st March 2015) - Stephens, Nathan A.; Skipworth, Richard J. E.; Gallagher, Iain J.; Greig, Carolyn A.; Guttridge, Denis C.; Ross, James A.; Fearon, Kenneth C. H.
Abstract: Background: In order to grow the potential therapeutic armamentarium in the cachexia domain of supportive oncology, there is a pressing need to develop suitable biomarkers and potential drug targets. This pilot study evaluated several potential candidate biomarkers in skeletal muscle biopsies from a cohort of upper gastrointestinal cancer (UGIC) patients. Methods: One hundred seven patients (15 weight‐stable healthy controls (HC) and 92 UGIC patients) were recruited. Mean (standard deviation) weight‐loss of UGIC patients was 8.1 (9.3%). Cachexia was defined as weight‐loss ≥5%. Rectus abdominis muscle was obtained at surgery and was analysed by western blotting or quantitative real‐time–polymerase chain reaction. Candidate markers were selected according to previous literature and included Akt and phosphorylated Akt (pAkt, n = 52), forkhead box O transcription factors ( n = 59), ubiquitin E3 ligases ( n = 59, control of muscle anabolism/catabolism), BNIP3 and GABARAPL1 ( n = 59, as markers of autophagy), myosin heavy‐chain (MyHC, n = 54), dystrophin ( n = 39), β ‐dystroglycan ( n = 52), and β ‐sarcoglycan ( n = 52, as markers of structural alteration in a muscle). Patients were followed up for an average of 1255 days (range 581–1955 days) or until death. Patients were grouped accordingly and analysed by (i) all cancer patients vs. HC; (ii) cachectic vs. non‐cachectic cancer patients; and (iii) cancer patients surviving ≤1 vs. >1 year post operatively. Results: Cancer compared with HC patients had reduced mean (standard deviation) total Akt protein [0.49 (0.31) vs. 0.89 (0.17), P = 0.001], increased ratio of phosphorylated to total Akt [1.33 (1.04) vs. 0.32 (0.21), P = 0.002] and increased expression of GABARAPL1 [1.60 (0.76) vs. 1.10 (0.57), P = 0.024]. β ‐Dystroglycan levels were higher in cachectic compared with non‐cachectic cancer patients [1.01 (0.16) vs. 0.87 (0.20), P = 0.007]. Survival was shortened in patients with low compared with high MyHC levels (median 316 vs. 1326 days, P = 0.023) and dystrophin levels (median 341 vs. 660 days, P = 0.008). Conclusions: The present study has identified intramuscular protein level of β ‐dystroglycan as a potential biomarker of cancer cachexia. Changes in the structural elements of muscle (MyHC or dystrophin) appear to be survival biomarkers.